Competitive Advantages of Agricultural Enterprises from the Perspective of the Analysis of the Competition’s Conditions - PYLYPENKO, Nadiia M.; PYLYPENKO, Viacheslav V.; KUCHKOVA, Kristina O. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).27, 2019)
The article is devoted to investigation of the problem of diagnosing competitive advantages of agricultural enterprise. The purpose of the article: deepening scientific and methodological approaches and practical recommendations on the development of a methodology for diagnosing the competitive advantages of an agricultural enterprise, which does not occupy a dominant position in the industry market. To assess competitive advantages, a method based on the theory of effective competition was used. Based on the peculiarities of the industry it is proposed to conduct diagnostics of competitive advantages from the position of market structure analysis, taking into account not only the peculiarities of the enterprise in terms of industry specificity, but also a type of market structure in the following areas: competitive advantages in the financial sphere, competitive advantages in the field of production, competitive advantages of personnel potential, market advantages of the enterprise. To assess the competitive advantages of small and medium-sized agricultural enterprises, it is proposed a methodical approach, which is to compare the enterprise's estimates with industry average values using the economic-mathematical function of Harrington's desirability. The proposed methodical approach, which was tested on the example of a private agricultural enterprise ‘Vil’ne’, allows you to quickly and objectively see the company's place in the industry market and eliminates duplication of individual indicators. The results of the analysis and assessment of competitive advantages enable the company to respond in a timely manner to identified problems by making adjustments to the developed competitive strategy.